Impact of repeated influenza vaccinations in persons over 65 years of age: A large population-based cohort study of severe influenza over six consecutive seasons, 2011/12–2016/17. Issue 37 (5th September 2018) - Örtqvist, Åke; Brytting, Mia; Leval, Amy; Hergens, Maria-Pia
Abstract: Background: A forty-year debate on the potential negative effects of repeated seasonal influenza vaccination has been inconclusive, with multiple observational studies of various design providing heterogeneous results too inadequate to inform vaccination policy. Methods: A large population-based cohort study including over one-million observations in individuals over age 65 from six consecutive seasons (2011/12–2016/17) in Stockholm County, Sweden. Current season vaccine effectiveness (VE) against severe, mostly hospital-attended, influenza was assessed using Cox multivariate regression analyses adjusting for demographic variables, comorbidities and previous seasonal influenza vaccination status. Results: In none of the six seasons was VE significantly different in persons vaccinated in the current season only, compared to those who had been vaccinated in both the current and the previous season. Neither were there any differences in VE during the seasons 2014/15–2016/17 when comparing persons vaccinated during the current season only vs. those vaccinated during one-three or four-five previous influenza seasons. In contrast, persons only vaccinated during one or more previous years had no protection during the current season. Conclusions: Persons above 65 years are the largest group at risk for severe or complicated influenza and policy should support their yearly seasonal influenza vaccination, which is to-date the best preventive measure available for all risk groups. No negative effects of repeated seasonal vaccination were seen in this large population-based cohort of older persons with severe influenza, which strengthens the recommendation that persons belonging to this age group should be vaccinated yearly.